Software engineering : a practitioner's approach - Pressman, Roger S. (McGraw-Hill, 2000)
This book is divided into five parts: The product and the process; Managing software projects; Conventional methods for software Engineering; Object-oriented software engineering; and Advanced topics in software engineering.